Digital Transformation of Sharia MSMEs in Cultivating an Entrepreneurial Spirit in the Digital Economy Era - Januari, Anas Tania; Nur Dwi Satrio, Sandy; Ariyanto, Yofi (AL-QARDH, 2024)
Digital transformation has changed the global economic landscape, including in the Sharia-based Micro, Small and Medium Enterprises (MSME) sector. This research aims to analyze the impact of digitalization on Sharia MSMEs and their role in fostering an entrepreneurial spirit in the digital economy era. By using a qualitative approach through literature study, this research identifies the challenges faced by Sharia MSMEs in adopting digital technology and explores strategies for integrating Sharia values with technological innovation. The research results show that digitalization has a positive impact on competitiveness, operational efficiency, and increased market access for Sharia MSMEs. Even so, challenges such as low digital literacy and limited resources are still the main obstacles. The integration of modern technology such as blockchain and sharia fintech has proven to be able to increase transparency, security and business efficiency. This research also emphasizes the importance of digital literacy and institutional support in strengthening an innovative and competitive Sharia entrepreneurial spirit, while still adhering to Islamic economic principles.Keywords: Digital Economy, Digitalization of MSMEs, Entrepreneurial Spirit, Islamic Economy